2022
DOI: 10.1186/s40981-022-00495-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequent tracheal suctioning is associated with extubation failure in patients with successful spontaneous breathing trial: a single-center retrospective cohort study

Abstract: Background Extubation failure, i.e., reintubation in ventilated patients, is a well-known risk factor for mortality and prolonged stay in the intensive care unit (ICU). Although sputum volume is a risk factor, the frequency of tracheal suctioning has not been validated as a predictor of reintubation. We conducted this study to examine whether frequent tracheal suctioning is a risk factor for reintubation. Patients and methods We included adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Patients with moderate to copious airway secretions had a > 3-fold risk of developing an extubation failure compared to those with minimal to no airway secretions. This is in line with many studies [ 11 , 13 , 16 , 27 , 28 ] conducted in different intensive care populations. This could be explained by the fact that an increase in the extent of secretions in the airway contributes to the decrement of mucociliary clearance, promotes accumulation of mucus, and potentially, airway obstruction [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients with moderate to copious airway secretions had a > 3-fold risk of developing an extubation failure compared to those with minimal to no airway secretions. This is in line with many studies [ 11 , 13 , 16 , 27 , 28 ] conducted in different intensive care populations. This could be explained by the fact that an increase in the extent of secretions in the airway contributes to the decrement of mucociliary clearance, promotes accumulation of mucus, and potentially, airway obstruction [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that the prolonged duration of intubation > 10 days was significantly associated with extubation failure compared with a shorter MV duration. In the same way, many studies reported that longer MV stays significantly increased the risk of developing EF [ 2 , 13 , and 34 ]. Evidence depicted that considering early tracheostomy for those patients anticipated to have prolonged intubation may avert the occurrences of EF [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 88%
“…Some foreign studies limit the time for re-intubation to within 24 h after extubation 11 , 12 , and the National Nursing Quality Platform has also adopted this time standard. Therefore, in this study, "pseudo" UEE is also defined as the absence of re-intubation within 24 h following an unplanned extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Chest care and toilette is an essential component in MV care, which include session of nebulizer followed by percussion and vibration then suction after flushing the endotracheal tube with normal saline and its implementation to address the amount of secretions more than 200cc/24 hours seems to be an important factor to reduce the failed extubation. No proof that a semi-quantitative airway care score (ACS) comprising six parts: spontaneous cough, gag, sputum quantity, sputum viscosity, suctioning frequency and sputum character in brain injured patients was found effective in prevention of failure of extubation (17). Hence, more research is needed to define an effective chest toilette that achieves successful extubation.…”
Section: Discussionmentioning
confidence: 99%